An Equitable Financing Management Model for Islamic Schools in Muslim-Minority Countries: A Comparative Study of AICS and EPIC Financing Policies in Australia - Anti Nur Mahmudah; Ari Pramono; Nabila Luthfia Syaharoh (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2026)
Educational financing constitutes a strategic dimension of Islamic school sustainability in Muslimminority countries because these institutions must balance financial sustainability, affordability, social equity, and the provision of education grounded in Islamic values. This study aims to develop an equitable financing management model for Islamic schools in Muslimminority countries through a comparative analysis of the financing policies of the Australian Islamic College of Sydney (AICS) and East Preston Islamic College (EPIC) in Australia. The study employs a qualitative design combining an integrative literature review with comparative document analysis. Data were obtained through a review of academic literature and analysis of the official financing policy documents of AICS and EPIC, which were purposively selected based on relevance, authenticity, and alignment with the research focus. Data were analyzed through stages of data condensation, categorization, comparison, synthesis, and model development, focusing on accessibility, social equity, transparency, payment flexibility, financial sustainability, governance, and progressive enforcement of financial obligations. The findings indicate that AICS places greater emphasis on concession mechanisms, scholarships, and social protection, whereas EPIC places greater emphasis on transparent discount structures, payment incentives, and procedural certainty. Synthesizing these approaches provides the basis for an Equitable Financing Management Model that integrates financial sustainability, educational accessibility, transparency, payment flexibility, and Islamic social justice, grounded in the Islamic principles of 'adl, amanah, and maslahah. The study contributes theoretically by extending the conceptualization of Islamic educational finance management toward equityoriented financial governance and practically by offering a framework that can inform Islamic schools in designing financing policies that are both sustainable and inclusive. Future research should assess the model through multiplecase studies, stakeholder interviews, family surveys, and financial data analysis to examine its applicability and transferability across diverse Muslimminority contexts.